Paradigma Good Governance Dalam Peningkatkan Kualitas Pelayanan Administrasi Kependudukan - Ricky Febriyano; Lukman Arif (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
The government in public services is expected to provide good services to the community so that the community needs effective and efficient time management. The Bojonegoro Regency Government received an award for excellent public service from the Ministry of State Apparatus Empowerment and Bureaucratic Reform. The aim to be achieved in this research is to determine the good governance paradigm in improving the quality of population administration services. This research uses a qualitative method with a descriptive approach to collect information based on the aim of describing the good governance paradigm in improving the quality of population administration services. The results of this research reveal that the good governance paradigm has been implemented well by the Bojonegoro Regency Population and Civil Registration Department. In the conclusion above, there are 9 principles of good governance which indicate that these principles have been implemented, but there is still two indicator of good governance principles that have not been implemented.